Perancangan Media Promosi Sekolah Berbasis Virtual Reality - Habibi, Muhammad Taufiq; Annas, Firdaus; Okra, Riri; Musril, Hari Antoni (Yayasan Lembaga Studi Makwa, 2023)
This research is based on the need for a PKL information system at Darul Ulum Muara Kiawai Vocational School, where the school does not yet have an information system capable of loading data and information related to PKL activities. So far, the school conveys information related to street vendors, which is still done orally and only relies on announcement paper, making it difficult for students who live far from school to receive information, as a result, the information received by students becomes less widespread and less efficient. Placement of students who do not match competence and delays in collecting street vendor reports are also one of the consequences of the absence of an information system that is able to accommodate data and information related to street vendor activities. The research method used is R&D (Research & Development), which is a research method that is useful for producing a product. The system development model in this study is the SDLC (System Develop Life Cycle) with the application of the Waterfall model with several stages such as communication, planning, modeling, construction and testing. Based on the research that has been done, the researchers succeeded in designing a SisfoPKL at Darul Ulum Muara Kiawai Vocational School. The results of the validity test carried out by computer experts stated that the product was valid with a value of 0.85. The results of practicality testing carried out by school staff and street vendors supervising teachers stated that the product was practical with a value of 0.85. The results of the effectiveness test conducted by 2 PKL supervising teachers, 1 school staff and 16 students stated that the product was effective with a value of 0.83. Abstrak Artikel ini dilatarbelakangi persoalan pendataan untuk kegiatan PKL di SMK Darul Ulum Muara Kiawai masih dilakukan secara manual, pihak sekolah dalam menyampaikan informasi terkait PKL masih dilakukan secara lisan dan hanya mengandalkan kertas pengumuman sehingga menyulitkan peserta didik yang berdomisili jauh dari sekolah dalam menerima informasi. Akibatnya informasi yang diterima peserta didik menjadi kurang meluas dan kurang efisien. Penempatan siswa PKL yang tidak sesuai kompetensi serta keterlambatan dalam pengumpulan laporan PKL juga merupakan salah satu akibat dari penggunaan sistem yang masih manual. Tujuan penelitian ini untuk merancang sebauh sistem informasi praktik kerja lapangan (PKL) di SMK Darul Ulum Muara Kiawai Pasaman Barat yang valid, praktis dan efektif. Metode penelitian yang digunakan adalah R&D (Research & Development) dengan model pengembangan SDLC (System Develop Life Cycle). Berdasarkan pada penelitian yang telah dilakukan, peneliti berhasil merancang SisfoPKL di SMK Darul Ulum Muara Kiawai. Hasil pengujian validitas yang dilaksanakan oleh ahli komputer dinyatakan bahwa produk valid dengan nilai 0,85. Hasil pengujian praktikalitas yang dilaksanakan oleh Staf sekolah dan guru pembimbing PKL dinyatakan bahwa produk praktis dengan nilai 0,85. Hasil pengujian efektifitas yang dilakukan oleh 2 guru pembimbing PKL, 1 staf sekolah dan 16 orang siswa dinyatakan bahwa produk efektif dengan nilai 0,83.